1994
DOI: 10.1128/jb.176.6.1586-1597.1994
|View full text |Cite
|
Sign up to set email alerts
|

Oscillating behavior of carbohydrate granule formation and dinitrogen fixation in the cyanobacterium Cyanothece sp. strain ATCC 51142

Abstract: It has been shown that some aerobic, unicellular, diazotrophic cyanobacteria temporally separate photosynthetic 02 evolution and oxygen-sensitive N2 fixation. Cyanothece sp. ATCC strain 51142 is an aerobic, unicellular, diazotrophic cyanobacterium that fixes N2 during discrete periods of its cell cycle. When the bacteria are maintained under diurnal light-dark cycles, N2 fixation occurs in the darlk Similar cycling is observed in continuous light, implicating a circadian rhythm. Under N2-fixing conditions, lar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
208
0

Year Published

2000
2000
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 183 publications
(219 citation statements)
references
References 39 publications
(56 reference statements)
11
208
0
Order By: Relevance
“…The expression of nitrogenase genes in Trichodesmium and in the intertidal or coastal marine unicellular cyanobacterium Cyanothece sp. strain 51142 has been shown to be under circadian control (Schneegurt et al, 1994;Chen et al, 1998;BermanFrank et al, 2001;Toepel et al, 2008). Genome-wide diel expression analysis may further elucidate the mechanism mediating the spatial/temporal segregation of oxygenic photosynthesis and N 2 fixation in diazotrophic cyanobacteria.…”
Section: Introductionmentioning
confidence: 99%
“…The expression of nitrogenase genes in Trichodesmium and in the intertidal or coastal marine unicellular cyanobacterium Cyanothece sp. strain 51142 has been shown to be under circadian control (Schneegurt et al, 1994;Chen et al, 1998;BermanFrank et al, 2001;Toepel et al, 2008). Genome-wide diel expression analysis may further elucidate the mechanism mediating the spatial/temporal segregation of oxygenic photosynthesis and N 2 fixation in diazotrophic cyanobacteria.…”
Section: Introductionmentioning
confidence: 99%
“…However, more recent studies revealed the existence of starch-like structures in unicellular diazotrophic cyanobacteria belonging to the order Chroococcales (Nakamura et al, 2005;Deschamps et al, 2008;Suzuki et al, 2013). The presence of anomalous glycogen particles had already been identified previously in this clade, while it is only very recently that this material was recognized as starch-like and the term "semiamylopectin" was coined to describe the major amylopectin-like fraction within these granules (Schneegurt et al, 1994;Suzuki et al, 2013). Four out of the six reported starch-accumulating cyanobacteria strains accumulate only this polysaccharide fraction.…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, in glycogen, the Glc of the outer chains may be easier to mobilize following fluctuations of physiology both in light and darkness. The crystalline starch-like granules, in turn, will offer a larger pool of osmotically inert carbohydrate stores for delayed use by nitrogenase or cell division at night (Schneegurt et al, 1994). It will be of interest to check for the presence of an analogous fraction in other starch-storing cyanobacteria.…”
Section: Cyanobacterium Sp Clg1 Accumulates Both Glycogen and Cyanophmentioning
confidence: 99%
“…This observation suggests that circadian cycles allow cellular processes to occur in a temporal sequence that is most beneficial to the organism. For example, some species of cyanobacteria (e.g., the genera Trichodesmium, Cyanothece, and Synechococcus) show a daily rhythm of photosynthesis that is in reverse phase to the daily cycle of nitrogenase expression, a key enzyme for nitrogen fixation Schneegurt et al, 1994;Huang et al, 1999). The peak of nitrogenase expression is during the dark phase of the cycle, allowing the temporal separation of expression of the oxygen-sensitive nitrogenase enzyme during periods when oxygen-evolving photosynthesis is not occurring.…”
Section: Rhythmic Clock Outputs In Cyanobacteriamentioning
confidence: 99%